Tomorrow’s Medicine Today: Nanomedicine in the Fight against Covid-19 - Steven Mufamadi; Mpho Ngoepe (The Thinker)
The coronavirus disease (Covid-19) caused by the SARS-CoV-2 virus has so far infected more than four million people worldwide, and the pandemic shows no signs of stopping. There is currently no known cure for Covid-19.